2021
DOI: 10.1155/2021/4877551
|View full text |Cite|
|
Sign up to set email alerts
|

The Evaluation and Its Key Influencing Factors Analysis of “Double First-Class” Universities’ Teaching Efficiency in China Based on SBM-DEA and Its Visual Decision Analysis System Development

Abstract: Based on a systematical summary of relevant research on university teaching efficiency, an evaluation index system was built to evaluate teaching efficiency of “Double First-Class” universities in China. The evaluation model to evaluate the teaching efficiency of these universities was built based on Slack-Based Measure model using Superefficiency Data Envelopment Analysis (SBM-DEA). Teaching efficiency of 36 “Double First-Class” universities had been evaluated after their assessment indexes data had been coll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…Nevertheless, teaching efficacy is crucial to teaching outcomes. It has been shown to have significant effects on job burnout [56], job satisfaction [57], organizational commitment [58], and turnover intention [59] and other variables among teachers, and is closely related to their emotional fluctuations [60]. Furthermore, teaching efficacy impacts students' academic achievement [61].…”
Section: Emotional Labor and Teaching Efficacy Of University Teachersmentioning
confidence: 99%
“…Nevertheless, teaching efficacy is crucial to teaching outcomes. It has been shown to have significant effects on job burnout [56], job satisfaction [57], organizational commitment [58], and turnover intention [59] and other variables among teachers, and is closely related to their emotional fluctuations [60]. Furthermore, teaching efficacy impacts students' academic achievement [61].…”
Section: Emotional Labor and Teaching Efficacy Of University Teachersmentioning
confidence: 99%
“…Shi et al [13] presented a similar study. Li et al [14] used the SBM-DEA evaluation model to evaluate the teaching efficiency across 36 "double first-class" universities. Wei and Zhang [15] compared the number of scientific publications by the "double first-class" universities from 2006 to 2018, and found that the absolute total number of articles published by Chinese universities increased in terms of quantity.…”
Section: "Double First-class" Construction Initiative and University ...mentioning
confidence: 99%
“…Tis article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. Tis investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%